ANALISIS HUBUNGAN MANAJEMEN PAJAK, SELISIH KURS DAN KEPEMILIKAN ASING DENGAN TRANSFER PRICING PERUSAHAAN - Renata Violetta Balkish; Trijoko Prasetyo; Basuki Wibowo (Faculty of Economics and Business, 2020)
Transfer pricing is the company's policy in determining the transfer price of related parties transaction. The purposed of this research is to get empirical evidence about the correlation of tax management, exchange rate, and foreign ownership with transfer pricing’s company. Independent variables used in this research are tax management, exchange rate and foreign ownership. Dependent variable of this research is transfer pricing. The population in this research are mining companies and miscellaneous industries listed on the Indonesia Stock Exchange (IDX) in 2014-2018. The method used for determining the sample is purposive sampling method.Sample consists of 67 observations. Data analysis using correlation pearson test with IBM SPSS Statistics 23 program as an analysis tool. The research results show that tax management has positive correlation with transfer pricing’s company.However, exchange rate and foreign ownership have no correlation with transfer pricing’s company.